2010 International Conference on Cyberworlds 2010
DOI: 10.1109/cw.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

User Model for Predictive Calibration Control on Interactive Screens

Abstract: Abstract-On interactive surfaces, a precise calibration of the tracking system is necessary for an exact user interaction. So far, common calibration techniques focus on eliminating geometric distortions. This static calibration is only correct for a specific viewpoint of one single user and parallax error distortions still occur if this changes (i.e. if the user moves in front of the digital screen).In order to overcome this problem, we present an empirical model of the user's position and movement in front o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The results confirm the findings in [4]. They showed that the user interacts mainly in the left partition of the screen in office environments.…”
Section: ) Measurement Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The results confirm the findings in [4]. They showed that the user interacts mainly in the left partition of the screen in office environments.…”
Section: ) Measurement Resultssupporting
confidence: 81%
“…We deduce a model for predicting the user's next interaction area from a user study on two synchronized large interactive stations. The results show that the interaction position is not -as initially assumed -simply Gaussian distributed around the last interaction position, since it depends on the use case as also proposed in [4].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast to the aforementioned types of parallax, we focus on the parallax error induced by large distances between the touchscreen and the display, which results in a displacement between the perceived and detected touch point on a touch-enabled public display. This was previously referred to as "parallax error" [28] or "visual parallax" [24]. Parallax was a major issue in touch-based interaction in the early days of touchscreens [34].…”
Section: Parallax In Public Displaysmentioning
confidence: 99%
“…Thus, the overlay's glass pane is in a certain distance to the matrix of the LC-screen. This results in a noticeable parallax distortion, which has a significant impact on the interaction precision of the user [18]. Small objects (targets) cannot be hit easily and the user has to continuously correct the position during his interaction.…”
Section: Hardware Implementationmentioning
confidence: 99%